2017
DOI: 10.18533/ijbsr.v6i12.1016
|View full text |Cite
|
Sign up to set email alerts
|

Golf Tourism: A Research Profile and Security Perceptions in Belek, Antalya, Turkey.

Abstract: <p>Our study aim to determine the current profile of sampled golf tourists visiting Belek, Antalya in high season and their perceptions of security using questionnaires to survey golf tourists in the sample were evaluated separately. The sample consisted of a survey profile of 280 golf tourists and their responses regarding security perceptions for Belek, Antalya. Chi-square testing and descriptive statistics were used to analyze the data. Despite some negative developments in Turkey (such as terrorist a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This is confirmed by many research which study golf tourism from various points of view, i.e. determining the level of satisfaction (Moital et al, 2013) and loyalty to the destination (Thanh et al, 2021), determining the developmental directions of golf tourism (Ersoy & Gülmez, 2014), determining the relationship between place attachment, golf tourism destination image, and revisit intention of golf tourists (Song et al, 2017), determining the profile of tourists and security perceptions of a destination (Aksu et al, 2016), observing the development of golf tourism from a sustainable point of view (López-Bonilla & López-Bonilla, 2016;López-Bonilla et al, 2018;Domínguez-Gómez and González-Gómez, 2017;Boukas & Ziakas, 2014), and many others. Research like these enable for golf tourism developers to rethink in which direction precisely they should focus when rethinking (golf) tourist offer development.…”
Section: Golf As a Part Of A Contemporary Tourist Product-an Insight mentioning
confidence: 77%
“…This is confirmed by many research which study golf tourism from various points of view, i.e. determining the level of satisfaction (Moital et al, 2013) and loyalty to the destination (Thanh et al, 2021), determining the developmental directions of golf tourism (Ersoy & Gülmez, 2014), determining the relationship between place attachment, golf tourism destination image, and revisit intention of golf tourists (Song et al, 2017), determining the profile of tourists and security perceptions of a destination (Aksu et al, 2016), observing the development of golf tourism from a sustainable point of view (López-Bonilla & López-Bonilla, 2016;López-Bonilla et al, 2018;Domínguez-Gómez and González-Gómez, 2017;Boukas & Ziakas, 2014), and many others. Research like these enable for golf tourism developers to rethink in which direction precisely they should focus when rethinking (golf) tourist offer development.…”
Section: Golf As a Part Of A Contemporary Tourist Product-an Insight mentioning
confidence: 77%
“…Olya et al (2017) research tourism concerning the culture in Turkey. The results of Aksu et al (2017) could also infer from the tourist profile of golf tourism for improving future tourism strategies in Antalya. Tourism can be affected by many parameters.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The study of golf tourism has emerged as an interesting research field [1], as very recent studies have demonstrated [14][15][16][17][18][19]. The present work tries to contribute to literature on the environmental attitudes and behaviours of golf tourists.…”
Section: Introductionmentioning
confidence: 93%